2008
DOI: 10.1089/thy.2007.0030
|View full text |Cite
|
Sign up to set email alerts
|

Hypothyroid Myopathy with Manifestations of Hoffman's Syndrome and Myasthenia Gravis

Abstract: Although hypothyroid myopathy is seen frequently and the relationship with autoimmune hypothyroidism and myasthenia gravis is well known, specific forms of hypothyroid myopathy such as Hoffman's syndrome (HS) are rarely described. Here we describe a 40-year-old patient with Hashimoto thyroiditis showing symptoms and signs of two discrete forms of hypothyroid myopathy (HS and myasthenic syndrome) together. To our knowledge this is the first reported case with features of both of these syndromes. We discuss the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
10
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 15 publications
2
10
1
Order By: Relevance
“…Treatment is levothyroxine supplement leads to remarkable results and subsidence of muscle hypertrophy in most of the cases[5111217] and the same was noted in our cases too. It was interesting to note that the hypertrophied, edematous muscles reduced in size and rather showed atrophy.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…Treatment is levothyroxine supplement leads to remarkable results and subsidence of muscle hypertrophy in most of the cases[5111217] and the same was noted in our cases too. It was interesting to note that the hypertrophied, edematous muscles reduced in size and rather showed atrophy.…”
Section: Discussionsupporting
confidence: 86%
“…[4] Presentation as a persistently isolated myopathy is extremely rare and HS is even rarer. [12349101112]…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Occasionally, Hashimoto's thyroiditis can even present with Hoffman's syndrome which characterised by proximal weakness and muscle hypertrophy 13. Turker et al 14 reported a case of Hashimoto's thyroiditis-induced myopathy with coexisting myaesthenic and Hoffman syndrome-like presentation. The other common causes of proximal weakness are vitamin D deficiency, Cushing syndrome, adrenal dysfunction and pituitary dysfunction.…”
Section: Discussionmentioning
confidence: 99%